2018
DOI: 10.3389/fpls.2018.00875
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping for Cold Tolerance in a Core Collection of Rice (Oryza sativa L.) Landraces by Using High-Density Single Nucleotide Polymorphism Markers From Specific-Locus Amplified Fragment Sequencing

Abstract: Understanding the genetic mechanism of cold tolerance in rice is important to mine elite genes from rice landraces and breed excellent cultivars for this trait. In this study, a genome-wide association study (GWAS) was performed using high-density single nucleotide polymorphisms (SNPs) obtained using specific-locus amplified fragment sequencing (SLAF-seq) technology from a core collection of landraces of rice. A total of 67,511 SNPs obtained from 116,643 SLAF tags were used for genotyping the 150 accessions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Most temperate or hardy plants have evolved specific strategies to survive low temperature, which involves a series of physiological, biochemical, molecular, and metabolic processes [3]. The multifaceted nature of the responses of the plant to cold stress and the intricate relationships between growth and response mechanisms, which in themselves are complex, dictate that cold tolerance is a highly complex, multigenic trait, as evidenced by a large number of quantitative trait locus (QTLs) that have been associated with cold tolerance [4,5]. Transcriptomic studies in model species under controlled conditions have indicated that the transcript abundances of hundreds of genes are altered under the imposition of cold stress [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most temperate or hardy plants have evolved specific strategies to survive low temperature, which involves a series of physiological, biochemical, molecular, and metabolic processes [3]. The multifaceted nature of the responses of the plant to cold stress and the intricate relationships between growth and response mechanisms, which in themselves are complex, dictate that cold tolerance is a highly complex, multigenic trait, as evidenced by a large number of quantitative trait locus (QTLs) that have been associated with cold tolerance [4,5]. Transcriptomic studies in model species under controlled conditions have indicated that the transcript abundances of hundreds of genes are altered under the imposition of cold stress [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of high interest to understand other putative roles, if there are any, of DNA markers associated with disease resistance. The significant association between a marker gene and a trait is widely applied using associa-tion mapping approach in many crops including rice (Song et al, 2018). Since the identification of R genes in Egyptian and Saudi Arabian rice has not been well-addressed, it is worthwhile to determine putative local rice genotypes that carry R gene(s).…”
Section: Introductionmentioning
confidence: 99%
“…The SLAF sequencing were conducted based on the standard protocol from Beijing Biomarker Technologies Corporation (http://www.biomarker.com.cn) and the introduction by Sun et al (2013) and Song et al (2018). To simplify, the first step was to perform a SLAF pre-design experiment with 8 accessions of landraces and different enzymes combinations.…”
Section: Methodsmentioning
confidence: 99%